PENGARUH KEPUTUSAN INVESTASI DAN KEPUTUSAN PENDANAAN TERHADAP NILAI PERUSAHAAN PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dian Mardianti Simanjuntak; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of investment decisions and funding decisions on company value in banking companies listed on the Indonesia Stock Exchange. The research period used is 2018-2020. This research is classified as a quantitative approach. The population in this study are all banking companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sampling technique used was purposive sampling. The data analysis technique used multiple linear regression. The results of this study indicate that investment decisions have a positive effect on firm value with a regression coefficient value of 0.002 and a significance value of 0.001. Funding decisions have no effect on firm value with a regression coefficient of -0.005 and a significance value of 0.927. Investment decisions and funding decisions have a effect on the value of banking companies listed on the Indonesia Stock Exchange with a calculated F value of 5.623 and a significance value of 0.005. The results of the adjusted R2 test in this study obtained a value of 0,135. This shows that firm value is influenced by investment decisions and funding decisions by 13.5%, while the remaining 86.5% is influenced by other factors not examined in this study Keywords: Company value, investment decision and funding decision